Correlates of time to clinical presentation for symptomatic individuals with gonorrhoea in South China: results from a cross-sectional study - Weiming Tang; Bin Yang; Cheng Wang; Juan Nie; Peizhen Zhao; Heping Zheng (BMJ Open)
Objectives This study aimed to determine the variation in the interval between the onset of symptoms and clinical presentation, and its associated factors among symptomatic individuals with gonorrhoea.Design A cross-sectional study was conducted between 1 June and 30 July 2017.Setting 129 sexually transmitted disease clinics from 21 cities of Guangdong, China.Participants Using convenience sampling method to recruit symptomatic individuals with gonorrhoea over 18 years old.Outcome measure Time to clinical presentation.Results Among 1664 participants, the median age was 29 (24–36) years old, and the majority were male (92.5%) and married (52.9%). The median time to clinical presentation was 3 (2–6) days. About 471 (28.3%) patients had sexual contact while symptomatic. After adjusting for covariates, participants who were female (aβ=0.44, 95% CI: 0.22 to 0.80), from east Guangdong region (aβ=0.44, 95% CI: 0.22 to 0.80) and had the absence of dysuria (aβ=0.26, 95% CI: 0.06 to 0.46) had increased time to clinical presentation. Participants who had commercial sex in the past 6 months (aβ=−0.11, 95% CI: −0.21 to –0.01) had decreased time to clinical presentation. Participants who were female (adjusted odds ratio (aOR)=1.66, 95% CI: 1.08 to 2.50) and delayed in seeking healthcare more than 7 days (aOR=46.71, 95% CI: 24.27 to 89.93) were more likely to have sexual contact while symptomatic.Conclusion The time to clinical presentation for individuals with symptomatic gonorrhoea is variable and a high proportion of participants continued to have sexual behaviour while symptomatic. Strategies to increase health literacy may help to minimise the sequelae of gonorrhoea and reduce onward transmission.